INDUSTRIAL ACTIVITY REVIEW OF THE FRENCH NETWORK OF PEDIATRIC CLINICAL INVESTIGATION CENTERS (FN-PCIC) 2008–2013. Issue 1 (14th December 2015) - Maksooud, Elsa; Jacqz-Aigrain, Evelyne
Abstract : Introduction: The French Network of Pediatric Clinical Investigations Centers (FN-PCIC) created in 2000 includes today 16 CIC grouped under the auspices of the INSERM and the corresponding public university hospitals. In response to the European pediatric regulation published in 2007, all pharmaceuticals laboratories, in order to complete their drug profile, must conduct pediatric clinical trials according to the Pediatric Clinical Investigation Plan and validated by the European Medicines Agency (EMA). This network plays a major role in facilitating and optimizing the conduction of nation-wide pediatric clinical trials. Therefore, the PN-CIC plays a major role to response to this acute demand in the pediatric field. The purpose of this review is to sum up the activity of the FN-PCIC between 2008 and 2013 and to analyze the impact of the European regulation. Methods: Only the industrial protocols will be analyzed, for every protocol a certain number of information was collected such as the pharmaceutical industry, the therapeutic fields, the phase of the study, the duration of the study, the methodology, and the number of patients needed. Results: 261 protocols were active during this period by 90 different sponsors. 218 were interventional studies and 43 were observational or non-drug studies (registers, post-AMM). The number of active studies was at 127 in 2013 compared to 76 in 2008. Furthermore, the total number of participations were 242 for 16 CIC in 2013 compared to 110 in 2008. The mean inclusion rate was 87%. The percentage of the common studies rises from 36% in 2008 to 50% in 2013. In addition, the feasibility study demands increased and were as high as 57, an average of one demand per week The inclusion percentage calculated using the data of the closed studies is at 87%. The therapeutic fields concerned were nephrology and oncology (15%), then neurology and pneumology (13%). Conclusion: Activity increased, linked to the national coverage now including 16 centers and high quality procedures to perform pediatric research trials under high ethical and quality standards.